HUBUNGAN ASUPAN KARBOHIDRAT DAN STATUS GIZI DENGAN TINGKAT KEBUGARAN JASMANI PADA ATLET BASKET REMAJA SISWA SEKOLAH MENENGAH PERTAMA - Haidar Rizqi; Ichwan udin (Media Gizi Indonesia, 2016)
Good physical ﬁ tness in athletes is essential in order to reach maximum performance during the game. Factors which affect the physical ﬁ tness are nutrition intake, nutritional status dan age. The role of carbohydrates in sports is very important to spare muscle glycogen during exercise. This study purpose was to analyze the correlation between carbohydrate intake, nutritional status and physical ﬁ tness in adolescent athletes of junior high school. This study used a cross-sectional study design. Total subjects in this study using a total population of about 37 people who are members of basketball team in junior high school 2 Ngamprah West Bandung District. Data of Carbohydrate intake was obtained through semi quantitative food frequency questionnaire method. Nutritional status was obtained by measuring body weight using digital bathroom scales and measuring height using microtoise tools. The average intake of carbohydrates was 375.4 grams which was 29.7% have a less carbohydrate intake and 70.3% have a adequate carbohydrate intake, average  BMI for age z-score was -0.166 SD as much as 2.7% have a very thin nutritional status, 5.4% have a thin nutritional status, 70.3% have a normal nutritional status, 13.5% overweight and 8.1% obese. The average ﬁ tness score was 14.9 (range 5-20) that means average they have a good physical ﬁ tness which was as much as 13.5% have a lack physical ﬁ tness and 86.5% have a good physical ﬁ tness. Results revealed that there is correlation between carbohydrate intake and physical ﬁ tness (p=0.025 and r= -0.367), nutritional status and physical ﬁ tness (p =0.038 and r = 0.342). The conclusion of this study is carbohydrate intake and nutritional status related to the physical ﬁ tness of adolescence basketballs athletes. Adolescent basketball athletes are advised to provide carbohydrate intake and maintain their nutritional status in the normal category in order to have good physical ﬁ tness.